Utilization of Maternity Waiting Home (MWH) to Improve Access to Health Services: Systematic Literature Review - Nuraina Nuraina (STIKes Patria Husada Blitar, 2020)
Maternity waiting home (MWH) is a home built in the compound or near to health facilities that provides standard medical and emergency obstetric care services. MWH is considered to be a key strategy to